Radical cystectomy and the implications of comorbidity. Issue 3 (March 2014) - Mayr, Roman; Fritsche, Hans-Martin; Pycha, Alexander; Pycha, Armin
<x xml:space="preserve">Abstract</x> Radical cystectomy (RC) with pelvic lymph node dissection constitutes the gold standard treatment for muscle-invasive urothelial carcinoma of the bladder and high-risk nonmuscle-invasive disease refractory to instillation therapy. Although RC is performed with curative intent, the overall 5-year survival has been reported to be as low as 62% in the current literature. Various clinicopathological parameters determine post-RC outcome, but besides these, the role of comorbidity has gained increasing attention. In the current clinical practice, comorbidity information is quantified using various evaluated comorbidity indices. In this paper, we discuss the most recent data on comorbidity and performance indices assessed in patients undergoing RC and highlight their clinical implications.